Optimizing snowboard cross and ski cross starts: a new laboratory testing and training tool - Raschner, C.; Platzer, H.-P.; Patterson, C.; Webhofer, M.; Niederkofler, A.; Lembert, S.; Mildner, E. (Science and Skiing IV, 2008)
INTRODUCTION: Snowboardcross and ski cross are now official Olympic events, so physical preparation of these athletes has become a focus in sport science. At least four racers start together so the start is crucial. Video analysis has shown that in many cases the two fastest Starters advance to the next round of competition. In short track speed skating, results are influenced both by ability and start position and these factors are even more important in the semifinals and finals where skill levels are more homogeneous (Maw et al., 2006). The goal of this project was to develop a start tool to optimize the start performance of world class athletes.